Influence of the complex compounds of Copper (II), Cobalt (II) and Zinc with aromatic and heterocyclic thioamides on the seeding properties of some agricultural cultures - Діденко, Н. О.; Ранський, А. П. (Scientific Progress & Innovations, 2018)
The influence of complex compounds of Copper (II), Cobalt (II) and Zinc with aromatic and heterocyclic thioamides on the seeding properties of the seeds of some agricultural plants has been studied. As potential plant growth promoters, the coordination compounds of Copper (II), Cobalt (II) and Zinc with deprotonated ligands based on aromatic (N-p-tolylthiobenzamide; N-p-anisylthiobenzamide) and heterocyclic (N-phenylpyridine-2-carbothioamide, N-p-phenylbenzimidazole-2-carbothioamide) thioamides have been investigated. In experiments, indole-3-acetic acid was used as a standard plant-growing regulator. To compare the plant-growing activity of pure thioamides with the corresponding coordination compounds, N-p-tolylthiobenzamide has been investigated. Control samples have not been processed by preparates. The plant-growing activity has been determined by the germination of the seeds, the increase of the mass of their seedlings, the length of the 2nd internode and the increase of the raw vegetative mass of some agricultural plants. The laboratory germination of the seeds of wheat, corn, sunflower and salad increased in comparison with the control sample in 1.10–1.48 times, with the standard – in 1.00–1.39 times and with the thioamide – in 1.00–1.14 times. It has been determined that the optimal concentration, in which the best parameters of plant-growing activity of the investigated compounds on seeds and seedlings of wheat, corn, sunflower and salad are recorded, is the concentration of 10 mg/l. In the greenhouse conditions we have studied the effect of the investigated compounds on the length of the second internode of the seedlings and the increase of the raw vegetative mass of bean germs after their treatment with doses of 4 mg/volume (5 kg/ha) and 0.025 mg/volume (0.031 kg/ha). According to the obtained results, the optimal dose of preparates has been determined – 0.031 kg/ha. Obtained results indicate that coordination compounds of Copper (II), Cobalt (II) and Zinc with aromatic and heterocyclic thioamides improve crop properties of the seeds and promote the formation of the vegetative mass of some agricultural plants. Among the studied compounds the highest plant-growing activity has been shown by the complex of Cobalt (II) with N-p-phenylbenzimidazole-2-carbothioamide.